2014
DOI: 10.1089/omi.2013.0100
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Berberine as a Multi-target Antimicrobial: A Multi-omics Study for Drug Discovery and Repositioning

Abstract: Postgenomics drug development is undergoing major transformation in the age of multi-omics studies and drug repositioning. Rather than applications solely in personalized medicine, omics science thus additionally offers a better understanding of a broader range of drug targets and drug repositioning. Berberine is an isoquinoline alkaloid found in many medicinal plants. We report here a whole genome microarray study in tandem with proteomics techniques for mining the plethora of targets that are putatively invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…Moreover, our data could help in depicting the molecular pathways governing the beneficial effects of a variety of plant derivatives used in traditional medicine [12, 5456]. Finally, we have to keep in mind that the global effect of BBR derivatives is strictly dependent on the experimental conditions and cell line tested; to generalize the observation made on colon cancer cells, we aim to extend the analysis to cell lines derived from other tumor types, expressing p53 either wt or mutated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data could help in depicting the molecular pathways governing the beneficial effects of a variety of plant derivatives used in traditional medicine [12, 5456]. Finally, we have to keep in mind that the global effect of BBR derivatives is strictly dependent on the experimental conditions and cell line tested; to generalize the observation made on colon cancer cells, we aim to extend the analysis to cell lines derived from other tumor types, expressing p53 either wt or mutated.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional arrays, for example, generate complex patterns of results that can be difficult to interpret [15,25]. A forerunner of the molecular biology approach was the examination of bacteria treated with test agent for changes to their morphology and ultrastructure [24].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products often exhibit antimicrobial activity against a wide range of pathogenic microorganisms. Recent advanced high-throughput multi-omics approaches integrating genomics, proteomics, and metabolomics have effectively accelerated the growth of antimicrobial research (Karaosmanoglu et al, 2014;Plichta et al, 2012;Wecke and Mascher, 2011). In addition, several research groups have reported that bacterial cell division process is one of the exciting targets for the development of next-generation antibiotics due to its conserved nature among the prokaryotes.…”
mentioning
confidence: 99%